Impact of Islamic Financing on Working Capital Management of Micro, Small, and Medium Enterprises in Tanjungpinang City, Indonesia - Firdaus; Sella Kurnia Sari; Deva Dwi Anggara (Department of Islamic Economics, Islamic University of Indonesia, 2022)
The purpose of this study was to analyze the effect of Islamic financing on the ability of working capital management of micro, small, and medium enterprises (MSMEs) in Tanjungpinang City, the Riau Islands Province, Indonesia. This study uses primary data that is processed quantitatively by using multivariate regression analysis using Stata. Primary data in this study were obtained from respondents using questionnaires, and secondary data were obtained from Statistics Indonesia. The research location in this study was Tanjungpinang City. The sample was determined using non-probability sampling with a sample of 125 MSMEs. Data collection techniques were carried out by conducting interviews and questionnaires. The results showed that the factors of musharakah and murabahah financing affect the variables such as average billing period, average payment period, cash turnover, and the ratio of current assets to total assets in MSMEs in Tanjungpinang City. MSMEs can adopt Islamic financial models to reduce operational costs by eliminating interest rates.